The Practice Innovation and Clinical Excellence Registry and the Eighth Joint National Committee - Ernesto Ledesma Sánchez; Carlos Alberto Hernández Rodríguez; Alexander Miguel Martínez Pérez; Alberto Morales Salinas (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
The Eighth Joint National Committee has several controversial aspects. One of them is the recommendation to raise the treatment goal in hypertensive patients over 60 years of age (with no history of diabetes or chronic kidney disease) to <150/90 mmHg. This paper discusses the results of a study from the Practice Innovation and Clinical Excellence Registry comprising 1,185,253 hypertensive individuals treated at US medical ambulatory services. It showed that approximately 15 % of the hypertensive meet the less stringent treatment goal of the Eighth Joint National Committee, but not the one recommended by the Seven Joint National Committee (<140/90 mmHg) and that this subgroup of hypertensive patients frequently face a high cardiovascular risk. The biases are also commented.